2021
DOI: 10.1002/ange.202012921
|View full text |Cite
|
Sign up to set email alerts
|

Silver in the Center Enhances Room‐Temperature Phosphorescence of a Platinum Sub‐nanocluster by 18 Times

Abstract: There has been controversy surrounding the roles of the metal core (metal–metal interaction) and the shell (metal–ligand interaction) in photoluminescence of ligand‐protected metal nanoclusters. We have discovered aggregation‐induced room‐temperature phosphorescence of a platinum–thiolate complex and its silver ion inclusion complex (a silver‐doped platinum sub‐nanocluster). The inclusion of silver ion boosted the photoluminescent quantum yield by 18 times. Photophysical measurements indicate that the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These considerations are even more dramatic when two different metal precursors are engaged, rendering the rational preparation of heterobimetallic entities extremely challenging. Postmodification strategies, such as doping of monometallic clusters with heterometal atoms, [25][26][27][28][29][30] or rearrangement of two independently synthesized monometallic clusters, [31][32][33] are emerging approaches that have attracted substantial interest recently, but so far limited to thiolate or carbonyl metal clusters. Lability phenomena and metal exchange strategies in polyhydride metal clusters is much less investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations are even more dramatic when two different metal precursors are engaged, rendering the rational preparation of heterobimetallic entities extremely challenging. Postmodification strategies, such as doping of monometallic clusters with heterometal atoms, [25][26][27][28][29][30] or rearrangement of two independently synthesized monometallic clusters, [31][32][33] are emerging approaches that have attracted substantial interest recently, but so far limited to thiolate or carbonyl metal clusters. Lability phenomena and metal exchange strategies in polyhydride metal clusters is much less investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…They ascribed the emission enhancement to the stabilization of charges on the LUMO orbital by the central Ag atom. Yamamoto et al 15 enhanced the emission quantum yield (QY) of a platinum-thiolate complex by 18 times through inclusion of an Ag atom into the Pt core. They demonstrated that the rigid crystallization structure and the reduced nonradiative decay rate are the main reasons that contribute to the emission enhancement of the silver-doped nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the rigid crystallization structure and the reduced nonradiative decay rate are the main reasons that contribute to the emission enhancement of the silver-doped nanoclusters. These prominent studies suggest that by properly manipulating the incorporation of another metal element, 13,16 in combination with the emerging assembly behavior of the derived nanoclusters, 15 the photoluminescence properties including QY and emission energy can be modulated effectively.…”
Section: Introductionmentioning
confidence: 99%
“…On a note, the PL properties of silver, copper, and other types of NCs are not covered in this review. [73][74][75][76][77][78][79][80][81][82][83][84][85][86]…”
Section: Introductionmentioning
confidence: 99%
“…On a note, the PL properties of silver, copper, and other types of NCs are not covered in this review. [ 73–86 ]…”
Section: Introductionmentioning
confidence: 99%